Delayed Infection after Immunization with a Peptide from the Transmembrane Glycoprotein of the Feline Immunodeficiency Virus - Richardson, J. (American Society for Microbiology (ASM), 1998)
Recent advances in the quantitative assessment of viral burden, by permitting the extension of criteria applied to assess the efficacy of vaccines from all-or-none protection to diminution of the viral burden, may allow the identification of original immunogens of value in combined vaccines. Peptides corresponding to three domains of the envelope glycoproteins of feline immunodeficiency virus that are recognized during natural infection were used to immunize cats. After challenge with a primary isolate of feline immunodeficiency virus, the development of acute infection was monitored by quantitative assessment of the viral burden in plasma and tissues by competitive reverse transcription-PCR, by measurement of the humoral response developed to viral components, and by lymphocyte subset analysis. Whereas immunization with two peptides derived from the surface glycoprotein had no effect on the early course of infection, immunization with a peptide derived from the transmembrane glycoprotein delayed infection, as reflected by a diminished viral burden in the early phase of primary infection and delayed seroconversion. This peptide, located in the membrane-proximal region of the extracellular domain, has homology to an epitope of human immunodeficiency virus type 1 recognized by a broadly neutralizing monoclonal antibody. These results suggest that lentivirus transmembrane glycoproteins share a determinant in the juxtamembrane ectodomain which could be of importance in the design of vaccines against AIDS.